Transmission of stimulus-induced epigenetic changes through cell division is coupled to continuous transcription factor activity - Sun, Sarah; Aguirre-Gamboa, Raúl; Barreiro, Luis B. (Frontiers in Immunology, 2023)
Trained immunity, or innate immune memory, has been attributed to the long-term retention of stimulus-induced histone post-translational modifications (PTMs) following clearance of the initial stimulus. Yet, it remains unknown how this epigenetic memory can persist for months in dividing cells given the lack of any known mechanism for stimulus-induced histone PTMs to be directly copied from parent to daughter strand during DNA replication. Here, using time course RNA-seq, ChIP-seq, and infection assays, we find that trained macrophages are transcriptionally, epigenetically, and functionally re-programmed for at least 14 cell divisions after stimulus washout. However, the epigenetic changes observed after multiple rounds of cell division do not result from the self-sustained propagation of stimulus-induced epigenetic changes through cell division. Instead, long-lasting epigenetic differences between trained and non-trained cells are always coupled with changes in transcription factor (TF) activity, emphasizing the central role played by TFs, and gene expression changes more broadly, in driving the transmission of stimulus-induced epigenetic changes across cell divisions.